2020
DOI: 10.1002/lary.28931
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient Factors and Management Strategies on Outcomes After Transverse Posterior Cordotomy

Abstract: Objectives/Hypothesis Carbon dioxide laser transverse posterior cordotomy (TPC) aims to improve airway aperture in patients with glottic obstruction. Postoperative complications may worsen airway compromise and necessitate additional interventions. We sought to identify factors impacting outcomes after TPC. Study Design Retrospective chart review. Methods Medical records of patients who underwent TPC for glottic airway obstruction at a tertiary‐care medical center between 2008 and 2018 were reviewed. Demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Twenty‐eight cordotomies were performed in our study, five of which resulted in readmission (18%). This rate is comparable to a study by Qazi et al where 5 out of 20 patients (25%) undergoing transverse posterior cordotomy required readmission for dyspnea 21 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Twenty‐eight cordotomies were performed in our study, five of which resulted in readmission (18%). This rate is comparable to a study by Qazi et al where 5 out of 20 patients (25%) undergoing transverse posterior cordotomy required readmission for dyspnea 21 …”
Section: Discussionsupporting
confidence: 86%
“…where 5 out of 20 patients (25%) undergoing transverse posterior cordotomy required readmission for dyspnea. 21 Our study found current/former smoking status to be a risk factor for readmission. Similarly, in their cordotomy study, Qazi et al also found that patients with a history of smoking were found to have a higher likelihood of experiencing complications after cordotomy procedures.…”
Section: Discussionmentioning
confidence: 54%
“…Prior studies have noted a relationship between smoking and tracheostomy dependence in patients with PGS, as well as poorer outcomes after surgical intervention for BVFI. 9,21 We did not elucidate a difference in tracheostomy status based on smoking history. This may be due to the fact that we described smoking as patients who had ever smoked at some point rather than as the current smoking status, since only five patients identified as current smokers.…”
Section: Discussionmentioning
confidence: 94%
“…It is not unusual for these patients to require multiple interventions until symptom resolution or significant improvement. [23][24][25][26] We present surgical interventions with increasing aggressiveness, which often correlates with the severity of stenosis being addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, they report 80% success with improvement in dyspnea and tracheostomy decannulation in a cohort of 20 patients with BVFP and PGS. 24 Arytenoidectomy is commonly performed endoscopically with the removal of the medial body of the arytenoid cartilage, widening the posterior glottic airway. A total or complete arytenoidectomy is the removal of the entire body of the arytenoid until flush with the wall of the cricoid ring.…”
Section: Adjuncts To Surgical Techniquementioning
confidence: 99%